PENGEMBANGAN BAHAN AJAR MATAKULIAH TEKNIK ANALISIS BIOLOGI MOLEKULAR (TABM) DI UNIVERSITAS NEGERI MALANG (UM) - Anis Noor Aini; Endang Suarsini; Mohamad Amin (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Students experiencing difficulty in learning and applying the material in the course of Engineering Analysis Molecular Biology (TABM) because it is abstract. To overcome these problems, the necessary teaching materials in the form of modules TABM to assist students in learning the material contained in the course. The process of preparation of the modulesadapt the model of R & D were prepared by Walter Dick and Lou Carey (Dick et al, 2009). Modules are developed then evaluated by two experts teaching materials with a minimum educational qualification S3 with teaching experience of more than 5 years, and 18 students who are candidates for S1 and have to take TABM a course at the State University of Malang (UM). Based on the results of an expert evaluation of teaching materials and students as a whole, it can be concluded that the introduction module components, content , and grammar demonstrated excellent qualifications module so it can be concluded that the module does not need to be revised and can be used as a teaching material support for TABM course in State University of Malang ( UM ) . Keywords:teaching material, module, TABM